DIGITAL PAYMENT AS A KEY ENABLER OF E-GOVERNMENT SERVICES: A CASE STUDY OF CHANDIGARH CITY (INDIA) - et al., Manjul Vaidya (International Journal of Control and Automation, 2020)
Going digital has been one of the primary priorities of Govt. of India. The study is limited to ChandigarhCity. The research is primarily focussed on evaluating citizens awareness, perception and concernsabout the adoption of digital payment system in the domain of e-government services. Primary data iscollected and empirically tested. The study also focussed on role of govt in reinforcing digital modesby Chandigarh citizens It has been observed that digital payment space is been increasingly occupiedby non-traditional players offering next generation products and services. Citizens services arefocussed in the research. The study found that e-sampark centers are very active in city. Study foundthat people prefer digital payments over traditional ways because of convenience primarily. MSampark needs to be strengthened. Connectivity of mobile phones and other related infrastructure needto be worked upon for smooth implementation of digital payments. Study found that city has lot ofpotential for successful implementation of Digital payment and receipt platform being availability ofmore young and educated population in the city. The study concluded that age, education andprofession have significant impact over awareness and usage of digital payment platform inChandigarh City.